A Study on Comparative Analysis of Infrastructure Funds - Dharmaraj, C (Journal of Commerce and Trade, 2010)
Companies raising funds for two purposes, ie., either for internal purpose or external purpose including investment activities. Now-a-days investment is a part of the activities of the corporate, especially, the firm who is having surplus funds in addition to the funds which is used for the normal course of business. The investors choosing the best investments proposals after taken into the consideration of three important investment principles, like safety, profitability and liquidity. In recent years the investors concentrating the blooming sectors especially infrastructure sector for their investment. Infrastructure is the buzzword in the present Indian context as there is a huge gap between demand and supply. Infrastructure funds are part of a mutual fund category called thematic funds. While sectoral funds invest in particular sectors like, information technology, power, metals, oil and gas, etc.,. Thematic funds invests in themes like infrastructure, consumption-led categories like the retail industry and outsourcing companies. Taken into the consideration of above the researchers have been analyzed three companies infrastructure funds to know the performance of each other. Acknowledgement: I would like to acknowledge and thank Mr. A Ragavendran, MBA Final Year Student, school of management, Karunya University, Coimbatore for extending immense help in every phase of writingthis article.